2010
DOI: 10.1203/pdr.0b013e3181d4ecc1
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome B-Lymphocyte Subpopulations, Intrinsic Defect or Decreased T-Lymphocyte Help

Abstract: Down syndrome (DS) is known for increased incidence of respiratory infections and autoimmune diseases, indicating impaired immunity. Until now, attention has been mainly focused on T lymphocytes. Therefore, we determined B-lymphocyte subpopulations in 95 children with DS compared with 33 age-matched control (AMC) children. DS serum immunoglobulin levels were compared with 962 non-DS children with recurrent infections. The results were combined with clinical data. Transitional and naive B lymphocytes are profou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 25 publications
5
65
0
2
Order By: Relevance
“…Finally, the impact of T21 on HSC/progenitors is likely to vary with age given the different patterns of hematopoietic abnormalities during fetal and postnatal life (11,13,15). Because we found that by 14-wk gestation, FL hematopoiesis is already perturbed, this raises the question of whether T21 also affects HSC/progenitor behavior during early embryonic development and in primitive hematopoietic cells, which is clearly extremely shown relative to GAPDH.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, the impact of T21 on HSC/progenitors is likely to vary with age given the different patterns of hematopoietic abnormalities during fetal and postnatal life (11,13,15). Because we found that by 14-wk gestation, FL hematopoiesis is already perturbed, this raises the question of whether T21 also affects HSC/progenitor behavior during early embryonic development and in primitive hematopoietic cells, which is clearly extremely shown relative to GAPDH.…”
Section: Discussionmentioning
confidence: 81%
“…These data show extensive dysregulation of B-cell development from HSC to mature B cells. Whether similar dysregulation of B-progenitor development persists beyond birth is unknown, but we hypothesize that "molecular resetting" of the fetal Blymphoid differentiation program contributes to B-cell immune deficiency (15) and B-ALL in children with DS (26).…”
Section: Discussionmentioning
confidence: 98%
“…Studies on the adaptive immune system of DS have shown that total lymphocyte numbers are decreased in this population (8)(9)(10)(11)(12)(13)(14). This holds true for the CD4 + and CD8 + T cell subsets, especially in the first 2 y of life, but becomes less pronounced with increasing age and eventually normalizes around the age of 16 y. Subdivision of T cells into naive and memory cells showed that in fact only the naive subsets are smaller compared with healthy controls (8,9,(11)(12)(13).…”
mentioning
confidence: 87%
“…For persons with Down syndrome aged <3 years, respiratory illnesses are the most common cause of hospital admissions [165], and respiratory disease is by far the most common cause of death in persons with Down syndrome [38]. Both intrinsic immune defects and extrinsic (anatomical) factors contribute to disturbed immune function and respiratory infection in individuals with Down syndrome [166][167][168]. Reduced numbers of T-and B-lymphocytes and abnormalities of their function both undoubtedly contribute to altered immunoglobulin levels, poor responses to vaccinations and increased respiratory infections [36,166,169,170].…”
Section: Immune System Disturbances Impacting Cardiopulmonary Functiomentioning
confidence: 99%